Allogeneic transplants of rib cartilage preserved in 98% glycerol or 70% alcohol into the malar process of rats: a comparative histological study. - Vieira, Eduardo Hochuli [UNESP]; Gabrielli, Marisa Aparecida Cabrini; Okamoto, Tetuo [UNESP]; Gabrielli, Mário Francisco Real [UNESP]; Scarso Filho, José [UNESP]; Ramalho, Lizati O. T. [UNESP]; Barbosa, Celso E. de Moraes [UNESP]; Marcantonio, Elcio [UNESP] (Nihon University School of Dentistry, 1993)
A comparative study was made of two methods of cartilage preservation, 98% glycerol and 70% alcohol. Rib cartilage was treated by either of these methods and transplanted into the malar process of rats. Cartilage grafts preserved by both methods were equally well tolerated. Resorption and bone substitution were similar in both groups after 120 days, although resorption was greater for the alcohol-preserved cartilage up until day 30. The possible reduction in antigenicity by the 98% glycerol did not produce any difference of behavior from the cartilage preserved in 70% alcohol.
Keywords: alcohol; glycerol; allotransplantation; animal; bone regeneration; cartilage; comparative study; drug effect; immunology; male; methodology; rat; rat strain; tissue preservation; transplantation; Animal; Bone Regeneration; Cartilage; Comparative Study; Ethanol; Glycerol; Male; Rats; Rats, Wistar; Support, Non-U.S. Gov't; Tissue Preservation; Transplantation, Homologous